Terpenes and fungal biomass in the nest mounds of Formica aquilonia wood ants - Sorvari Jouni; Hartikainen Samuel (Elsevier Masson, 2022)
Abstract
Nest mounds of wood ants of the Formica rufa group are built using conifer needles, small branches, other plant materials and soil. Conifer needles contain several mono and sesquiterpenes. Thus, wood ant nests may act as terpene hotspots in conifer forest soils. Some of the terpenes show antifungal activity and may thus cause small-scale heterogeneity in fungal biomass. We compared terpene concentrations and fungal biomass (ergosterol concentration) of nest material of the wood ant Formica aquilonia from the top, core and basement of 14 nest mounds in eastern Finland. Overall, α-pinene, camphene, sabinene, β-pinene, myrcene, limonene, camphor and longifolene were detected the most and were commonly present in all the studied layers. We found that terpene concentrations differed between the sampled nest material layers, being generally highest in the core of the nest and lowest at the basement of the nest. There was no association between the terpene concentration and material moisture. Fungal biomass was highest in the top layer, intermediate in core and lowest in basement; however, it was not negatively associated with terpene concentrations. Fungal biomass in nest mounds was positively associated with moisture and alkalinity. Nest mounds of Formica rufa group wood ants are complex structures with different chemical and microbial properties among its layers.